Synthetic Effect of Vivid Shark Skin and Polymer Additive on Drag Reduction Reinforcement. (23rd June 2014) - Chen, Huawei; Zhang, Xin; Che, Da; Zhang, Deyuan; Li, Xiang; Li, Yuanyue
Abstract : Natural shark skin has a well-demonstrated drag reduction function, which is mainly owing to its microscopic structure and mucus on the body surface. In order to improve drag reduction, it is necessary to integrate microscopic drag reduction structure and drag reduction agent. In this study, two hybrid approaches to synthetically combine vivid shark skin and polymer additive, namely, long-chain grafting and controllable polymer diffusion, were proposed and attempted to mimic such hierarchical topography of shark skin without waste of polymer additive. Grafting mechanism and optimization of diffusion port were investigated to improve the efficiency of the polymer additive. Superior drag reduction effects were validated, and the combined effect was also clarified through comparison between drag reduction experiments.